2013
DOI: 10.3390/cryst3030391
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Study and Intermetallics Formation in Gold and Copper Wire Bonding in Microelectronics Packaging

Abstract: A comparison study on the reliability of gold (Au) and copper (Cu) wire bonding is conducted to determine their corrosion and oxidation behavior in different environmental conditions. The corrosion and oxidation behaviors of Au and Cu wire bonding are determined through soaking in sodium chloride (NaCl) solution and high temperature storage (HTS) at 175 °C, 200 °C and 225 °C . Galvanic corrosion is more intense in Cu wire bonding as compared to Au wire bonding in NaCl solution due to the minimal formation of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 15 publications
(19 reference statements)
0
34
0
1
Order By: Relevance
“…Otherwise, it was proved experimentally that thin Al pad (≈ 1 µm thickness) can prevent gold and copper corrosion, because intermetallics formation rate in Au-Al system is much more higher than intermetallics formation rate in Cu-Al system, so it is possible to use Cu instead of Au for wire bonding in microelectronics packaging, and Cu has higher electric conductivity, higher thermal conduction, and lower material cost than Au [2]. It was founded experimentally, that copper electric corrosion is higher than aluminium electric corrosion in approximately two times at temperatures less than 40 о С [3,4], so thin Al layer can prevent copper electric corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, it was proved experimentally that thin Al pad (≈ 1 µm thickness) can prevent gold and copper corrosion, because intermetallics formation rate in Au-Al system is much more higher than intermetallics formation rate in Cu-Al system, so it is possible to use Cu instead of Au for wire bonding in microelectronics packaging, and Cu has higher electric conductivity, higher thermal conduction, and lower material cost than Au [2]. It was founded experimentally, that copper electric corrosion is higher than aluminium electric corrosion in approximately two times at temperatures less than 40 о С [3,4], so thin Al layer can prevent copper electric corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of its excellent electrical conductivity, chemical stability, and corrosion resistance, gold is widely used as an electronic sliding contact material for high precision inertial devices, satellite slip ring brushes, robots, etc. [ 1 , 2 , 3 , 4 , 5 ]. However, the low intrinsic hardness, easy deformation, and poor elasticity of pure gold limits its application in circumstances necessitating high mechanical strength requirements [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mass conservation law gives: , (1) so three phases general thickness is approximately greater in two times than initial Cu cover thickness. Otherwise, it was proved experimentally that thin Al pad (≈1 µm thickness) can prevent gold and copper corrosion, because intermetallics formation rate in Au-Al system is much more higher than intermetallics formation rate in Cu-Al system, so it is possible to use Cu instead of Au for wire bonding in microelectronics packaging, and Cu has higher electric conductivity, higher thermal conduction, and lower material cost than Au [2]. Corrosion and intermetallics rate formation in gold and copper wire bonding in microelectronics packaging were investigated in [2] at temperatures T1=175 о С, T2=200 о С, and T3=225 о С during 120, 240, 360, and 480 h. The authors have reported that crosssectional analysis of the Cu ball on Al pad confirmed that corrosion occurred at temperatures about T=200 о С primarily beneath the Cu balls and did not initiate from the Al pad, formation of CuCl2 didn't allow self-passivation of Cu to occur, so rate of copper corrosion increased, and the rate of Cu-Al intermetallics formation was found to be three to five times slower than Au-Al intermetallics formation at all three annealing temperatures.…”
Section: Introductionmentioning
confidence: 99%